Optimizing the management of locally advanced pancreatic cancer with a focus on induction chemotherapy: Expert opinion based on a review of current evidence. (July 2019) - Seufferlein, Thomas; Hammel, Pascal; Delpero, Jean Robert; Macarulla, Teresa; Pfeiffer, Per; Prager, Gerald W.; Reni, Michele; Falconi, Massimo; Philip, Philip A.; Van Cutsem, Eric
Highlights: Locally advanced pancreatic cancer is generally considered incurable. Induction chemotherapy may downstage the tumour in some patients. Induction chemotherapy can allow some patients to achieve successful resection. Trials are underway to evaluate modern chemotherapies as induction therapy. Research is needed to identify the best induction regimens and suitable patients. Abstract: Surgical resection of pancreatic cancer offers a chance of cure, but currently only 15–20% of patients are diagnosed with resectable disease, while 30–40% are diagnosed with non-metastatic, unresectable locally advanced pancreatic cancer (LAPC). Treatment for LAPC usually involves systemic chemotherapy, with the aim of controlling disease progression, reducing symptoms and maintaining quality of life. In a small proportion of patients with LAPC, primary chemotherapy may successfully convert unresectable tumours to resectable tumours. In this setting, primary chemotherapy is termed 'induction therapy' rather than 'neoadjuvant'. There is currently a lack of data from randomized studies to thoroughly evaluate the benefits of induction chemotherapy in LAPC, but Phase II and retrospective data have shown improved survival and high R0 resection rates. New chemotherapy regimens such as nab –paclitaxel + gemcitabine and FOLFIRINOX have demonstrated improvement in overall survival for metastatic disease and shown promise as neoadjuvant treatment in patients with resectable and borderline resectable disease. Prospective trials are underway to evaluate these regimens further as induction therapy in LAPC and preliminary data indicate a beneficial effect of FOLFIRINOX in this setting. Further research into optimal induction schedules is needed, as well as guidance on the patients who are most suitable for induction therapy. In this expert opinion article, a panel of surgeons, medical oncologists and gastrointestinal oncologists review the available evidence on management strategies for LAPC and provide their recommendations for patient care, with a particular focus on the use of induction chemotherapy.